The Role of Islamic Religious Education in Overcoming The Moral Crisis of Generation Z in the Midst of Globalization - Hengki Yulhafiz Elva; Eva Dewi; Siti Maulidiya Agustin; Idham Kholis (Universitas Negeri Semarang, 2026)
Background - Digital globalization has had a significant impact on the lives of Generation Z, both positively and negatively. One concerning effect is the emergence of a moral crisis characterized by moral degradation, weakening social ethics, an identity crisis, and low self-control in dealing with the rapid flow of information and global culture. Purpose - This study aims to examine the forms of moral crisis experienced by Generation Z, analyze the role of Islamic religious education in shaping moral values and character, and identify effective educational strategies to address the moral crisis amid globalization. Method/approach - This study employs a literature review method by analyzing various scientific journal articles, academic books, and other relevant scholarly sources related to Islamic religious education, Generation Z morality, and globalization challenges. The data were analyzed using a descriptive-qualitative approach through systematic and narrative synthesis of previous research findings. Findings - The findings indicate that Islamic religious education plays a strategic role as a moral safeguard through the internalization of faith values, the cultivation of noble character, the strengthening of social and digital ethics, and the reinforcement of Generation Z’s religious identity. Furthermore, contextual learning strategies, exemplary educators, the positive use of digital media, curriculum strengthening, and continuous moral guidance have proven effective in addressing the moral crisis. Conclusions - This study confirms that strengthening adaptive and integrative Islamic religious education is an urgent necessity in shaping a morally grounded and well-characterized Generation Z that is prepared to face the challenges of globalization. Novelty/Originality/Value - The novelty of this study lies in integrating Islamic religious education with contextual and adaptive approaches to the digital era as a strategic solution to overcome the moral crisis among Generation Z.